Geotechnical characteristics of clayey soil stabilized with fly ash and marble dust - Zeybek, Abduelhakim; Tanyildizi, Muhammed; Tosun, Ismail; Cabalar, Ali Firat (Elsevier, 2025)
This study investigates the separate and combined impacts of Class-F fly ash (FA) and marble dust (MD) on the geotechnical properties and resilient modulus (MR) of clayey soil. An intensive series of laboratory tests, including plasticity, swelling-shrinkage, compaction, unconfined compressive strength (UCS), shear strength, California Bearing Ratio (CBR), cyclic triaxial, and microstructural analyses, were conducted on soil specimens containing FA and MD at different percentages varying from 0 % to 12 %. The results showed that FA and MD additions significantly reduced the plasticity, free swell, and linear shrinkage potential of the soil, whilst UCS and CBR values increased up to a threshold value of 6 % to 9 % and then declined. The incorporation of FA, MD, and their combination (FA + MD) enhanced the soil's CBR by approximately 45.1 %, 55.9 %, and 85.1 %, respectively. Similarly, the UCS of the soil cured for 7 days improved by 14.1 %, 44.0 %, and 72.5 %, respectively. The cyclic triaxial tests yielded the highest MR values with FA alone, leading to a 51.1 % increase. When FA and MD were used together, MR values increased by 31.6 %, which was relatively higher than the 28.1 % increase observed with the use of MD alone. Furthermore, statistical modeling to predict the MR values was proposed, evaluated comparatively with already available applications, and hereby confirmed its superiority over traditional models to save time for future researchers.
Keywords: Clayey soil; Fly ash; Marble dust; Stabilization; Resilient modulus